2018
DOI: 10.3892/ijmm.2018.3501
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention with mesenchymal stem cells prevents nephropathy in diabetic rats by ameliorating the inflammatory microenvironment

Abstract: Diabetic nephropathy (DN) is a major complication of diabetes and represents the leading cause of end-stage renal disease. Mesenchymal stem cell (MSC) treatment has been demonstrated to be effective in DN models by reducing albuminuria and attenuating glomerular injury; however, limited in-depth understanding of the underlying mechanism and a lack of clinical trials hinders its clinical use. Additionally, most of these experimental studies were conducted on the advanced stage of nephropathy, which is difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 47 publications
2
65
0
Order By: Relevance
“…Furthermore, MSCs were demonstrated to increase α-synuclein removal in Parkinson's disease by increasing autophagy (25). In addition, Li et al (26) demonstrated that early intervention with MSCs prevented renal injury by ameliorating the inflammatory microenvironment in diabetic rats and Tang et al (27) reported that MSCs alleviate acute renal injury by suppressing the C5a/C5a anaphylatoxin chemotactic receptor-NF-κB signaling pathway. The results of the present study suggested that hUC-MSCs enhanced HK-2 cell autophagy and inhibited the PI3K/AKT/mTOR signaling pathway, which demonstrated a protective role of hUC-MSC in the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MSCs were demonstrated to increase α-synuclein removal in Parkinson's disease by increasing autophagy (25). In addition, Li et al (26) demonstrated that early intervention with MSCs prevented renal injury by ameliorating the inflammatory microenvironment in diabetic rats and Tang et al (27) reported that MSCs alleviate acute renal injury by suppressing the C5a/C5a anaphylatoxin chemotactic receptor-NF-κB signaling pathway. The results of the present study suggested that hUC-MSCs enhanced HK-2 cell autophagy and inhibited the PI3K/AKT/mTOR signaling pathway, which demonstrated a protective role of hUC-MSC in the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, lipopolysaccharide (LPS)-stimulated macrophages produced more IL-10 when cultured with bone-marrow MSCs; however, this effect was eliminated if the bone-marrow MSCs lacked the genes encoding TLR-4, myeloid differentiation primary response gene-88, tumor necrosis factor-a (TNF-a), or Cox-2, 37 and in diabetic rats, MSC treatment upregulated anti-inflammatory cytokine IL-10. 38 MSCs appear to play a dual role whereby they promote the M1 differentiation of naive M F , yet in the presence of M1, MSCs promote the M1 to M2 conversion in MSC-M1 cocultures. 39 The differentiation of specific MSC/ M F cell phenotypes is closely related to the surrounding environment that acts as an orchestrator of immune activity.…”
Section: Immune Function and Inflammationmentioning
confidence: 99%
“…Lang et al reported 6 deaths of model rats during the construction of diabetes model [22] while Wang et al reported 1 death in both MSCs-treated group and DN group besides 2 deaths because of anesthesia [16]. In the study of Li et al, there was 1 rats dead in the DN group and 2 in the MSCs-treated group [27]. During a 12-…”
Section: Search Resultsmentioning
confidence: 99%
“…Glucose was almost detected after the MSCs treatment, except for 2 studies [27,32]. Sixteen studies measured glucose for once at the end of the experiment [13-16, 18-24, 26, 28-31].…”
Section: Assessment Of Glucosementioning
confidence: 99%
See 1 more Smart Citation